Survey of cassava virus diseases in Tanzania - Legg, James P.; Raya, M. (Informa UK Limited, 1998)
A survey was carried out of African cassava mosaic geminivirus and cassava brown streak virus diseases (ACMD and CBSD) in Tanzania. ACMD occurred throughout the country at low to moderate incidences in the fifteen different regions surveyed (1- 64%). The incidence was generally higher along the coastalplain than in higher altitude areas in the interior. There was a significant correlation between numbers ofadults ofthe whitefly vector, Bemisia tabaci, and incidence of recently infected plants ( R = 0.77, p < 0.01), although most infection was attributable to the use of infected cuttings. CBSD was more restricted in distribution and, where present, incidence was low to moderate (1- 36%). Cassava plantings along the southern border with Mozambique link the highest incidence area on the south-east coast near Mtwara, with the other important area ofCBSD incidence along the shore ofLake Malawi. The effects of climatic parameters on ACMD and CBSD incidence are discussed. The survey data suggest that both diseases could be controlled in Tanzania by the use of phytosanitation which involves the use of disease-free planting material and the removal (roguing) of diseased plants.